?ISOLATION AND IDENTIFICATION OF A FLAVONOL GLYCOSIDE USING HIGH SPEED COUNTER CURRENT CHROMATOGRAPHIC TECHNIQUE FROM THE LEAVES OF SALVADORA PERSICA (Biological Sciences - PJSIR, 2000)
This paper introduces the results of separation of a crude flavonoid sample, separated and identified as Kaempferol 3-a-L- rhamnosyl-7-P-xylopyranoside 1 alongwith Quercetin and Kaernpferolfrom the 10%EtOH extract of the leaves of Salvadora persica through centrifugal partition chromatography (Pharma-TechCCC-I000 Instrument)using upper phase as mobile phase and solvent system CHCll; MeOH; EtOH; Hp (5:3:3:4). Detection was carried out at 254nm with flow rate 3ml/min and a rotational speed 800rpm.Three flavonoidpeakswereresolvedandelutedoutin3.5h.The resultsobtained with thepresent CCC method are substantially far better than those from the conventional Column chromatography in terms of peak resolution and separation time, furthermore, separations are much improved.